Nasopharyngeal tuberculosis - A case report - Monteiro, Daniel (2012)
Tuberculosis (TB) is the most common infectious disease in the world. It has many different types of manifestations, being able to affect many organs and resembling other pathologies, including carcinomas. It´s presentation in the nasopharynx is very rare and the main symptom is cervical lymphadenopathies. A case of a 16 year old boy with nasopharyngeal tuberculosis is reported. The diagnostic was difficult to achieve because of the rare location and due to negative test results. The patient was administered tuberculostatic drugs and total regression of symptoms and signs was observed after 9 months. More often than wanted, only after a therapeutic test is the diagnosis made. It is important to consider TB has a differential diagnosis in patients with nasopharyngeal masses and cervical lymphadenopathies.